Prediction of Student Academic Performance using Artificial Neural Network - SUBRAMANIAM, KAUSALIYA (IRC, 2019)
Despite of providing high quality on education, demand on predicting student academic performances become more critical to improve on quality and assisting student to achieve a great performance in their studies.